Development of a multi-arm polyrotaxanes modified mesoporous silica-coated gold nanoplatform for protecting endothelial progenitor cells against high glucose environment. (January 2022) - Cao, Duanwen; Zuo, Huihua; Jiang, Mingjin; Huang, Yiteng; Li, Liang; Lin, Fengxia; Liu, Yue
Recent study reported that endothelial progenitor cells (EPCs) have potential to treat diabetic macroangiopathy. High glucose environment of diabetes can affect the adhesion of EPCs by decreasing the expression of CXC chemokine receptor 4 (CXCR4) and affect the proliferation of EPCs by decreasing the expression of miR-126. The results showed that the cytotoxicity of GNR@MSNs@PEI to EPCs was significantly lower than PEI; the temperature of GNR@MSNs@PEI solution can be controlled between 38–40°C under 808 nm laser irradiation. 25.67 µg of pcDNA3.1-GFP-CXCR4 and 5.36 µg of FITC-miR-126 could be loaded in 1 mg of GNR@MSNs@PEI; GNR@MSNs@PEI has gene transfection almost the same as Lipofectamine 3000. Subsequent in vitro studies showed that pcDNA3.1-GFP-CXCR4 and miR-126 loaded GNR@MSNs@PEI can significantly increase the adhesion and proliferation and decrease the apoptosis of EPCs treated with high glucose under 808 nm laser irradiation. In conclusion, nano-carriers (GNR@MSNs@PEI) with high pcDNA3.1-CXCR4 and miR-126 loading capacity, high biocompatibility, well cell internalization, and controllable release ability were constructed to transfer CXCR4 expression plasmid (pcDNA3.1-CXCR4) and miR-126 into EPCs efficiently. Further in vitro studies indicated that pcDNA3.1-CXCR4 and miR-126-loaded GNR@MSNs@PEI could protect EPCs against high glucose-induced injury.